Evaluation of polyethylene glycol phosphate aqueous two-phase systems in purifying pepsin from residues of the slaughter house - Alberto, Maryen; Farruggia, Beatriz (Cuban Journal of Agricultural Science, 2016)
system in pepsin separation, different purification systems formed by polyethylene-glycol (PEG) and potassium phosphate were evaluated. The study was conducted on enzyme homogenates of porcine gastric mucus (PH) and bovine abomasum homogenates (BH). Different molecular mass of polyethylene - glycol (1500 and 3000) and distribution of temperature (8 and 20 °C) were evaluated. The distribution of the pure enzyme was first determined, and then, the performance of the enzyme in the homogenates. The enzyme yield and the purification factor were determined for each system. The pepsin distribution in both homogenates showed similar performance to the pattern enzyme and distribution constants higher than the unit (PH 2.7 and BH 1.5) were obtained. The purification indicators for both preparations showed a purification factor higher than 3(HP 3.25 and BH 3.81) and yields higher than 60 % (PH 74.16 and BH 61. 54). The system formed by PEG 1500/phosphate at a distribution temperature of 20 ºC was the best variant. This method of separation and purification of pepsin is a simple and rapid alternative, also allows obtaining an adequate purity for further extractives steps of the enzyme. Key words: enzymes, purification systems, homogenates